Pre-CCRT 18-fluorodeoxyglucose PET-CT improves survival in patients with advanced stages p16-negative oropharyngeal squamous cell carcinoma via accurate radiation treatment planning - Tsung-Ming Chen; Wan-Ming Chen; Mingchih Chen; Ben-Chang Shia; Szu-Yuan Wu (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Purpose No large-scale prospective randomized study with a long-term follow-up period has evaluated the survival outcomes of preconcurrent chemoradiotherapy (CCRT) 18-fluorodeoxyglucose positron emission tomography–computed tomography (18FDG PET–CT) in patients with non–human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC). Patients and Methods We included patients with stage I–IVA p16-negative OPSCC receiving definitive CCRT and categorized them into two groups according to pre-CCRT 18FDG PET–CT and compared their outcomes: the case group consisted of patients who underwent pre-CCRT 18FDG PET–CT, whereas the comparison group consisted of patients who did not receive pre-CCRT 18FDG PET–CT. Results The final cohort consisted of 3942 patients (1663 and 2279 in the case and comparison groups, respectively). According to multivariable Cox regression analysis, pre-CCRT 18FDG PET–CT was not a significant prognostic factor for overall survival in patients with stages I–II of p16-negative OPSCC receiving standard CCRT. The adjusted hazard ratio (95% confidence interval) of all-cause death for the patients with advanced stages (III–IVA) of p16-negative OPSCC receiving pre-CCRT 18FDG PET–CT was 0.75 (0.87–0.94, P = 0.0236). Conclusions Routine use of pre-CCRT 18FDG PET–CT is not necessary for each patient with p16-negative OPSCC. Pre-CCRT 18FDG PET–CT is associated with improved survival in patients with stage III–IVA p16-negative OSCC, but might be not in those with stage I–II p16-negative OPSCC. Condensed abstract No large-scale prospective randomized study with a long-term follow-up period has evaluated the survival outcomes of preconcurrent chemoradiotherapy (CCRT) 18-fluorodeoxyglucose positron emission tomography–computed tomography (18FDG PET–CT) in patients with p16-negative oropharyngeal squamous cell carcinoma (OPSCC). Our study is the first, largest, homogenous modality study on PET–CT including a long-term follow-up cohort to examine the survival outcomes of pre-CCRT 18FDG PET–CT or non-pre-CCRT PET–CT for patients with p16-negative OPSCC receiving standard CCRT stratified by different clinical stages. Routine use of pre-CCRT 18FDG PET–CT is not necessary for each patient with p16-negative OPSCC. Pre-CCRT 18FDG PET–CT is associated with improved survival in patients with stage III–IVA p16-negative OPSCC, but might be not in those with stage I–II p16-negative OPSCC.